Revolution of AI in Aquaculture and Fish Processing: A Review - Mohammed, Imran; Hepzibah Blesslene, R.; Vimaladevi, S.; Harini, S.; Alamelu, V.; Mohamed Faizullah, M.; Brita Nicy, A.; Praveenkumar, P. (International Journal of Bio-resource and Stress Management, 2025)
The application of Artificial Intelligence (AI) in aquaculture and fish processing remains underexplored and underutilized. This review aims to provide a comprehensive overview of current and emerging AI technologies in these sectors, evaluating their accuracy, practicality, and potential for sustainable and economical implementation. The objective is to highlight AI’s transformative role and encourage its adoption among fish farmers, processors, and other stakeholders to improve productivity and operational efficiency. AI is revolutionizing the aquaculture and fish processing industries by enhancing efficiency, reducing labour costs, and promoting sustainable practices. Traditional methods in these fields often demand intensive manual labour, increasing production costs and limiting scalability. The integration of AI technologies enables real-time monitoring, automation, and data-driven decision-making, which significantly reduces labour dependency and enhances precision. In aquaculture, AI applications include fish growth monitoring, disease detection, and environmental control, using machine learning algorithms and IoT-based systems to optimize operations. In fish processing, AI-driven tools support tasks such as sorting, grading, filleting, and packaging, ensuring consistent product quality and safety. These advancements not only streamline production but also reduce waste and improve resource utilization. This review presents recent developments and success stories of AI implementation in aquaculture and fish processing, illustrating its potential to modernize the industry. By fostering smarter and more sustainable practices, AI can contribute significantly to boosting productivity, improving economic outcomes, and supporting food security goals in the fisheries sector.